The development of emotional competence in adolescent - Nasef Enad, Shaimaa; Ameer Abd Ali, Marwaa (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims at finding out the progress of the emotional competence of the teenagers whose ages are 12, 13, 14, 15, and 16 years as well as exploring the significant differences in the effective efficiency of the sex and age variables. To achieve the aim of the study , the researcher has designed a scale for effective efficiency that consists of 47 items. A sample of 400 male and female teenagers has been chosen randomly; then, the psychometric factors of the scale have been secured, including validity and reliability. The researcher has come up with the following results: 1. Teenagers of (15) years have effective efficiency 2. Effective efficiency is considered a progress factor (constructive) for the ages (12, 13, 14, 15, and 16) years, and this fact is assured by the theories of the progressive stages. 3. The progress of the effective efficiency is affected by the sex variable since girls are faster in the progress of the effective efficiency than boys. In the light of the results and the conclusions, the researcher has written some suggestions and recommendations.